The transformational leader role in achieving organizational commitment among vocational training employees - Benlokrichi , Nourdine; bouattit , Sofiane (Journal of Social Sciences and Humanities, 2021)
With the global transformations taking place in the current century, the countries of the world have endeavored to seriously anticipate the future of this century and keep pace with the so-called leaders ’industry, where fluctuations and tangible changes at the global level foretell that the leaders’ industry is a feature of the current era, which is the primary concern of organizations that seek to reserve their position in the ranks The future, as organizations fail often due to the absence of competent leaders, because the leadership style plays a fundamental role affecting individuals ’performance and their organizational commitment .The current study aimed to know the role of the transformational leader in achieving organizational commitment among employees The National Institute specialized in vocational training, Taibi Rabeh, in the municipality of Bousadaa. A descriptive approach was adopted in analyzing the data to answer the following questions : - Is there a correlation between the traits of a transformational leader and organizational commitment in the study sample? - Is there a correlation between the characteristics of the transformational leader and (emotional commitment, normative commitment, continuous commitment) in the study sample? - Are there differences in the level of organizational commitment of the study sample due to variables (gender, academic level, professional experience)?